2011
DOI: 10.1111/j.1365-2702.2011.03704.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a multi‐faceted training intervention on the improvement of hand hygiene and gloving practices in four healthcare settings including nursing homes, acute‐care geriatric wards and physical rehabilitation units

Abstract: This study underscored the usefulness of implementing contextualised training programs, while more traditional courses have shown little impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
1
19
0
1
Order By: Relevance
“…Hand hygiene is recognised to be one of the simplest and most effective ways to decrease transmission of infections, and the practice of appropriate adherence is important (Castle et al, ). However, the results in this study are in line with a French study conducted in eight different settings for elderly (61.2%; Eveillard et al, ). Three other studies have reported significantly lower hand hygiene adherence in long care facilities in elderly and nursing homes, respectively, 14.7% in Hamilton, Ontario, 17.5% in Italy and 11.3% in Taiwan (Liu, Liang, Wu, & Chuang, ; Pan et al, ; Smith, Carusone, & Loeb, ).…”
Section: Discussionsupporting
confidence: 92%
“…Hand hygiene is recognised to be one of the simplest and most effective ways to decrease transmission of infections, and the practice of appropriate adherence is important (Castle et al, ). However, the results in this study are in line with a French study conducted in eight different settings for elderly (61.2%; Eveillard et al, ). Three other studies have reported significantly lower hand hygiene adherence in long care facilities in elderly and nursing homes, respectively, 14.7% in Hamilton, Ontario, 17.5% in Italy and 11.3% in Taiwan (Liu, Liang, Wu, & Chuang, ; Pan et al, ; Smith, Carusone, & Loeb, ).…”
Section: Discussionsupporting
confidence: 92%
“…Three studies were at low risk for all criteria [18,25,26]. One study was at high risk for three criteria [27]. Lack of consideration of confounding variables created a high risk of bias in three of the seven non-randomized trials [27e29].…”
Section: Non-randomized Trialsmentioning
confidence: 99%
“…Studies on the effectiveness of multifaceted hand hygiene programs have shown some effectiveness. For example, a study in a Taiwan NH showed that nursing assistants had significantly more knowledge and better compliance after hand hygiene training [51]. Moreover, a recent study conducted in four healthcare settings (acute care geriatric wards, skilled NHs and physical rehabilitation units), demonstrated a significant improvement for hand hygiene and gloving practices [52].…”
Section: Challenges To Infection Prevention Programs: Old and Newmentioning
confidence: 99%
“…Strategies to prevent new acquisition of AROs and curb their transmission in the NH setting include education of HCWs, targeted surveillance and feedback, facility-appropriate antibiotic stewardship programs and diligent hand hygiene [9,11,34,38,51,53]. Hand carriage by HCWs can result from direct contact with residents’ secretions during care or indirect contact with their environment.…”
Section: Challenges To Infection Prevention Programs: Old and Newmentioning
confidence: 99%